Dynamics of Changes from the Abajadun Numbers to the Ghubari System - Dina Nur Amilah Balbisi; Ahmad Izzuddin (Universitas Islam Negeri Mataram, 2025)
The numbering system has undergone significant evolution along with the development of human civilization. One form of a numerical system with historical and symbolic value is the Abajadun numerals that associate Arabic letters with certain numerical values. However, along with the increasing need for efficiency in scientific calculations and documentation, especially in astronomy and mathematics, there was a transition to the Ghubari numeral system. This paper attempts to trace the history of the shift in using Abajadun numerals to modern numerals. In addition, this study examines the influence of Middle Eastern culture on the use of Abajadun numerals in various contexts, especially in astronomy and astrology. This study uses a qualitative approach with historical methods to examine the transition from the Abajadun numeral system to the Ghubari system. The results show that Abajadun numerals were used in various fields such as astronomy, astrology, administration, and mathematics before being replaced by more practical Indian numerals. The process of transmitting knowledge and trade in the Persian region during the reign of Khosru Nusirwan played an important role in the spread of the Ghubari numerals. In conclusion, this study reveals that the Abjadun numbering system does not merely function as a counting tool but reflects a cosmology of numbers that is integrated with the classical Arab-Islamic intellectual tradition. The transition from the Abjadun to the Ghubari system marks a crucial point in the history of number epistemology, where efficiency, clarity of notation, and compatibility with the development of arithmetic and astronomy became urgent needs